Analysis of the relationship between contingency factors and management accounting practices adopted in the light of contingency theory: a study in hotels in the municipalities of Recife and Ipojuca in the state of Pernambuco - Samara Lima Sobrinho; Aldo Leonardo Cunha Callado (Revista Ambiente Contábil)
Purpose: The objective of this study is to analyze the relationship between contingency factors and management accounting practices adopted by hotels located in the municipalities of Ipojuca and Recife, in the state of Pernambuco.